The impact of project-based learning with e-modules on mathematical communication skills - Anisatul Farida; Ratna Puspita Indah (Universitas Sarjanawiyata Tamansiswa, 2024)
In the context of enhancing students' mathematical communication skills, innovative teaching methods such as project-based learning (PBL) integrated with E-modules offer promising results. This research aims to assess the impact of project-based learning (PBL) using E-modules on mathematical communication skills, specifically in understanding graphic representations. The research population consists of third-semester students in the Informatics Engineering program at Universitas Duta Bangsa, Surakarta, during the 2023/2024 academic year. The sample includes all 40 students from class 22A1. The measurement tools used in this study are learning achievement tests and mathematical communication ability tests. Data were analyzed using simple regression analysis with the product-moment correlation coefficient formula. This study employs correlation analysis to examine the relationship between the independent variable, Project-Based Learning using E-modules (X), and the dependent variable, mathematical communication skills (Y). The results show that project-based learning with E-modules has a strong positive correlation of 76% with students' mathematical communication skills. However, 24% of the variance in students' communication skills is influenced by other factors. This study concludes that integrating PBL with E-modules is highly effective in enhancing students' mathematical communication skills. Nonetheless, additional factors such as self-efficacy and mathematical reasoning also play significant roles in improving these skills.